What Italian Defense Attorneys Know about Factors Affecting Eyewitness Accuracy: A Comparison with U.S. and Norwegian Samples - Magnussen, Svein; Safer, Martin A.; Sartori, Giuseppe; Wise, Richard A. (Frontiers in Psychiatry, 2013)
We surveyed 100 Italian defense attorneys about their knowledge and beliefs about factors affecting eyewitness accuracy. The results of similar surveys show that U.S. defense attorneys were significantly more knowledgeable than other legal professionals, including U.S. prosecutors and U.S. and European judges. The present survey of Italian defense attorneys produced similar results. However, the results suggest that the defense attorney’s superior performance may be due at least in part to their skepticism of eyewitness testimony rather than their greater knowledge of eyewitness factors.